Effect of lower body explosive power on sprint time in a sled-towing exercise - Martinez-Valencia, M. A.; Linthorne, N. P.; Alcaraz, P. E. (Science & Sports, 2013)
Introduction: This study investigated the correlation between lower body explosive power and the rate of increase in sprint time with increasing sled weight in a sled-towing exercise. Synthesis of the facts: Eight male sprinters performed tests of lower body explosive power. The rate of increase in sprint time showed a strong correlation with countermovement jump height (r = -0.73) and with normalized peak power in a countermovement jump (r = -0.81) and a squat jump (r = -0.80). Conclusion: Inter-athlete differences in the rate of increase in sprint time might be due to differences in the athlete's power-to-weight ratio.